Perancangan dan Pengembangan Video Katalog Film Animasi Indonesia - Dhanar Intan Surya Saputra; Anwar Budhi Dharmawan; Didit Suhartono; Doni Fajar Ramadan; Ikhwan Fahrial Selofianto; Argiyan Dwi Pritama (PT FORMOSA CENDEKIA GLOBAL, 2022)
Many Indonesian animations on YouTube are not directly proportional to the National Gross Domestic Product for the Creative Economy sub-sector data. The film, animation, and video sub-sector still considered low and has not contributed much and, caused by many factors, such as not being correctly recorded by animation creators. There are many efforts to record the content creators, such as government involvement, the Associations (AINAKI), stakeholders, and academics. Seeing these problems, we conducted a data through YouTube scraping to be able to find content creator channels of animations. Then we present it in the form of a video catalog of Indonesian animated films. This final video is delivered in 5 minutes, with production stages including pre-production, production, and post-production.